The Diagnostic Value of Compression Ultrasonography in Patients with Suspected Recurrent Deep Vein Thrombosis - Prandoni, Paolo; Lensing, Anthonie WA; Bernardi, Enrico; Villalta, Sabina; Bagatella, Paola; Girolami, Antonio; for the DERECUS Investigators Group (Thrombosis and Haemostasis, 2002)
Diagnosis of recurrent deep-vein thrombosis (DVT) is difficult because of limitations in distinguishing acute from old thrombi. In the past, an ultrasound method for diagnosis of recurrent ipsilateral DVT was developed, which relies on repeated measurements of the diameters of the common femoral and popliteal veins. To assess the safety of withholding anticoagulation from patients with improved or stable compression vein diameters, 205 consecutive patients presenting with suspected recurrent ipsilateral DVT were evaluated. The vein diameter was measured under compression with the transducer and compared with earlier ultrasound results. Patients with stable or improved ultrasound findings had repeat ultrasound assessments after 2 (± 1) and 7 (± 1) days. Patients with repeatedly normal ultrasound results were followed-up for six months to determine the incidence of symptomatic recurrent venous thromboembolism.Of the 205 patients, 153 had stable or improved ultrasound findings. Repeat ultrasound assessment became abnormal in 3, and recurrence was confirmed by venography in all. A six months follow-up was done in the remaining 150 patients with repeatedly normal ultrasound tests and showed 2 (1.3%; 95% CI, 0.02 to 4.7%) confirmed non-fatal venous thromboembolic complications. The positive predictive value of a stable or improved ultrasound was 90% (95% CI, 77 to 97%).In conclusion, it is safe to withhold anticoagulant treatment from patients with suspected recurrent ipsilateral DVT in whom compression ultrasonography showed improved or stable vein diameters.
Keywords: DVT; thrombi; ultrasonography